Aortic Interruption Presenting with Recurrent Ischemic Strokes in an Adult. Issue 2 (17th January 2012) - Vural, Atay; Arsava, Ethem M.; Ozgen, Burce; Oguz, Kader K.; Efe, Orhan; Demircin, Metin; Topcuoglu, Mehmet A.
ABSTRACT Presentation of an interrupted aortic arch (IAA) in adulthood is extremely rare. Nonhemorrhagic stroke has not been reported previously in any adult with IAA. We, herein, describe a formerly asymptomatic 52‐year‐old male presenting with recurrent vertebrobasilar circulation ischemic strokes resulting from accelerated atherosclerotic arteriopathy secondary to IAA associated upper body hypertension. Surgical correction of IAA led to treatment of hypertension and cessation of ischemic attacks together with regression of collateral arterial networks as shown by computer tomography angiography.